PEMBUATAN GAME PLATFORMER BEYOND MENGGUNAKAN UNITY DENGAN XBOX 360 CONTROLLER - Muliadi Muliadi; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Beyond is a Post Apocalyptic Sci-fi Platformer game made with Unity 2D Engine. Players follows the adventure of Teeby, a robot courier entrusted with a key to call the humans in the outer space back to the long forgotten earth. Player can jump, sprint and wall jump to overcome any obstacles in the way to reach the final destination. There are components that become elements of games such as enemy, interactive object, and environment. Testing is done with questionnaires filled in by 30 respondents. Tests results showed that “Beyond” is very challenging with great character designs and fun to play.